2016
DOI: 10.4103/0019-509x.204763
|View full text |Cite
|
Sign up to set email alerts
|

A review of squamous cell carcinoma arising in mature cystic teratoma of the ovary

Abstract: Squamous cell carcinoma in MCT of ovary is a rarity. It carries a poor prognosis, especially in advanced stages and suboptimally cytoreduced patients. Platinum with or without taxane based chemotherapy may be useful as adjuvant treatment. However, further studies and standardization of treatment protocols are required for any recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Age-wise distribution of these cases is mentioned below in table no.1. Name of the study Year of publication Numbers of cases reported Age of occurrence Santwani PM et al [6] 2008 01 40 years Gupta V et al [10] 2009 02 30 years, 65 years Bashyal R et al [3] 2012 03 33 years, 51 years, 60 years Suna Avc1 et al [9] 2012 01 52 years Gupta N et al [4] 2014 01 65 years Ranu Patni [11] 2014 01 53 years Mardi K et al [12] 2014 01 68 years Yarmohammadi H et al [13] 2014 01 48 years Rekhi B et al [14] 2015 12 Median age = 49 years Sharma S et al [1] 2015 01 66 years Abhilasha N et al [8] 2016 10 Median age = 53.5 years Srivastava H et al [2] 2017 01 30 years Goudeli C et al [7] 2017 01 54 years ~ 323 ~ Indulkar ST et al [5] 2018 01 40 years Maharjan S [15] 2019 In our present study, painful enlargement or distension of abdomen is the presenting complaint of the patient herself. Similar complaints have been reported in other case studies also like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Santwani PM et al [6] , etc.…”
Section: Discussionmentioning
confidence: 99%
“…Age-wise distribution of these cases is mentioned below in table no.1. Name of the study Year of publication Numbers of cases reported Age of occurrence Santwani PM et al [6] 2008 01 40 years Gupta V et al [10] 2009 02 30 years, 65 years Bashyal R et al [3] 2012 03 33 years, 51 years, 60 years Suna Avc1 et al [9] 2012 01 52 years Gupta N et al [4] 2014 01 65 years Ranu Patni [11] 2014 01 53 years Mardi K et al [12] 2014 01 68 years Yarmohammadi H et al [13] 2014 01 48 years Rekhi B et al [14] 2015 12 Median age = 49 years Sharma S et al [1] 2015 01 66 years Abhilasha N et al [8] 2016 10 Median age = 53.5 years Srivastava H et al [2] 2017 01 30 years Goudeli C et al [7] 2017 01 54 years ~ 323 ~ Indulkar ST et al [5] 2018 01 40 years Maharjan S [15] 2019 In our present study, painful enlargement or distension of abdomen is the presenting complaint of the patient herself. Similar complaints have been reported in other case studies also like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Santwani PM et al [6] , etc.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received optimal cytoreduction followed with adjuvant chemotherapy seem to have a good outcome with longer survival. [8,9] Optimal cytoreduction can bring a mean survival of 14 months while 7.8 months in suboptimal cases. [10] Kikkawa et al [6] reported a 79% 5-year-survival rate for patients without residual disease compared with 10.1% for those with residual disease.…”
Section: Treatment Of Ovarian Sccmentioning
confidence: 99%
“…On account of the activity of cisplatin in ovarian cancer and gynaecological squamous-cell carcinomas, chemotherapy with cisplatin and taxane became a common therapy in SCC, and have been extended progression-free interval in most patients. [3,8,11,12] Patients received adjuvant chemotherapy (mostly platinum-based) appeared to survive longer than those who had surgery only. [4,13] Several studies suggested that chemotherapy with BEP can be used in ovarian SCC.…”
Section: Treatment Of Ovarian Sccmentioning
confidence: 99%
“…Ovarian germ-cell tumors account for $ 20% of all ovarian neoplasms, and for 2% of all ovarian malignancies. [1][2][3] Mature cystic teratomas (MCTs) are the most common ovarian germcell tumors, accounting for $ 70% of benign ovarian tumors in women under 30 years of age, [4][5][6] and they are composed of totipotent cells developing into well-differentiated ectodermal, endodermal, and mesodermal tissue. 7 Ectodermal derivatives, which include keratinizing epidermis, sebaceous and sweat glands, hair follicles and neuroectodermal tissues, are often the most prominent.…”
Section: Introductionmentioning
confidence: 99%